A Review on Khubbāzī (Malva sylvestris L.): Phytochemical, Pharmacological Properties and Therapeutic Applications - Habib, Abdul; Kalam, Mohd Afsahul; Ahmad, Riyaz; Aziz, Abdul; Avid, Mohammad; Ahmad, Belal (Journal of Complementary and Alternative Medical Research, 2024)
Traditional system of medicine, especially Unani, highly value Khubbāzī (Malva sylvestris L.) for its therapeutic properties. Its leaves, seeds and flowers are utilized medicinally as Barg-i-Khubbāzī, Tukhm-i-Khubbāzī and Gul-i-Khubbāzī since time immemorial. It is used in Unani Medicine for various activities like concoctive, diuretic, anti-inflammatory, hepatoprotective, hence used to treat several ailments related to respiratory, skin and digestive systems such as cough, cold, coryza, sore throat, chronic bronchitis, intestinal ulcer and urinary issues like strangury, irritation in micturition etc. Pharmacological studies on various parts of the plant have been reported such as hepatoprotective, antioxidant, anti-inflammatory etc. which are supported by the bioactive compounds, alkaloid, glycosides, flavone etc. present in the plant. Scientific studies validated several actions documented in Unani literature, but further researches needed to explore the hidden properties of the plant. This review focuses on the plant’s traditional uses, pharmacological properties.